Structure and growth of araucaria forest in southern Brazil - Costa, Emanuel Arnoni; Hess, André Felipe; Guimarães Finger, César Augusto (Bosque (Valdivia), 2017)
The growth of individual trees can be simulated by multiplying a function that describes the potential by another modifier, the “modifying-potential”. Modeling of the potential function for trees growing without competition determines the limit of optimum growth to species, while a modifying function sets the decrease component taking in consideration the influence of environmental factors. Thus, the aim of the study was to adjust the modifier function to describe the periodic increment in the basal area of Araucaria angustifolia trees in sites with Araucaria Forest in southern Brazil. For this, we sampled 397 individual trees. Dendrometric and morphometric variables, competition indices and increment in diameter with the chronology of widths of the growth ring were measured. Periodic increment in basal area was described by a logarithmic function that explained 57 % of variance and correlated with the diameter at the beginning of the period, height, variable of crown size and competition indices. Results indicate that the modifier function can be used accurately to explain changes in growth and spatial and temporal structure of the species in the Araucaria Forest.